Light, shade and shadow - Koller, E. L. (Edmund Leonard), b. 1877. (Mineola, N.Y. : Dover, 2008)
Even the most beautiful drawing can appear flat without shading. But with this expert guide, every artist can learn how to add dimension to their work. Beginning with the basics - casting light on simple geometric shapes - and progressing to the human figure, these step-by-step techniques, illustrations, and exercises show how to achieve dramatic effects with light and shadow.
An unabridged republication of Light and shade : prepared especially for home study, originally published by International Textbook Company, Scranton, Pa., in 1937.
Keywords: Drawing -- Technique; Drawing -- Study and teaching; Shades and shadows in art